Assessment of public expenditure efficiency: A review - Wong, Sing Yun (Penerbit UUM, 2022)
Public spending is considered an important tool in a government's continuous efforts to improve the delivery of the public sector and achieve growth objectives. The increasing demand for higher expenditures may create a tax burden and pressurised the budgetary allocation. This leads to the rising concern to evaluate the efficiency and effectiveness of public expenditure. A highly efficient public sector will likely be able to produce more outputs with less spending on inputs. Hence, the primary aim of this paper is to provide a comprehensive review of the growing literature on public expenditure efficiency. Against this background, an extended review will be discussed on the determinants that influence the efficiency of public spending. As such, the objective of this paper can be summarised to address the following key questions. Firstly, how to measure the efficiency and effectiveness of public expenditure? Secondly, what are the determinants that influence the efficiency of public spending? The answers to these questions will help solve the recent problem of budget constraints faced by policymakers.